Investigation on Association and Expression of ESR2 as a Candidate Gene for Boar Sperm Quality and Fertility - Gunawan A. (2014)
ESR2 is involved in oestrogen-related apoptosis in cell cycle spermatogenesis but their effects have not yet confirmed in pig. Therefore, this study was aimed to investigate the association of ESR2 polymorphism with sperm quality and boar fertility traits and to analyse the ESR2 mRNA and protein expressions in boar reproductive tissues. DNA samples from 203 Pietrain (PI) and 100 Pietrain×Hampshire (PIHA) pigs with records of sperm quality [sperm concentration (SCON), motility (MOT), semen volume (VOL), plasma droplet rate (PDR) and abnormal spermatozoa rate (ASR)] and fertility [non-return rate (NRR) and number of piglet born alive (NBA)] traits were available. A SNP in coding region of ESR2 g.35547A>G in exon 5 was associated with MOT and PDR in the PI and with SCON, VOL, MOT and PDR in PIHA population. For mRNA and protein expression study, a total of six boars were divided into two groups with group I (G-I) and group II (G-II) where G-I characterized for relatively a better sperm quality according to the mean of two groups. mRNA expression was higher in brain and testis than that in all parts of epididymis. Both qRT-PCR and western blot analysis revealed that the ESR2 gene expression and protein expression were significantly higher in testis collected from G-II compared with that of G-I boars. Moreover, ESR2 protein localization in germ cell, Leydig and Sertoli cells, epithelial cells and spermatozoa was remarkable, which indicated the important role of ESR2 in spermatogenesis process. These results might shed new light on the roles of ESR2 in spermatogenesis as candidate for boar fertility, but still the lack of association across populations should be considered. © 2011 Blackwell Verlag GmbH.